2019
DOI: 10.5713/ajas.18.0683
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphorus deficiency impaired growth, intestinal digestion and absorption function of meat ducks

Abstract: ObjectiveAn experiment was conducted to investigate the effects of dietary non-phytate phosphorus (nPP) deficiency on intestinal pH value, digestive enzyme activity, morphology, nutrient utilization, and gene expression of NaPi-IIb in meat ducks from 1 to 21 d of age.MethodsA total of 525 one-d-old Cherry Valley ducklings were fed diets (with 7 pens of 15 ducklings, or 105 total ducklings, on each diet) with five levels of nPP (0.22%, 0.34%, 0.40%, 0.46%, or 0.58%) for 21 d in a completely randomized design. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Numerous studies have demonstrated that reduced dietary nPP levels can decrease growth performance and nutrient availability in poultry ( Adeola, 2018 ; Xu et al., 2019 ), consistent with the findings of the present study. One reason for the decrease in the growth performance of ducks fed a P-deficient diet was the higher Ca: nPP ratio in such diets.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Numerous studies have demonstrated that reduced dietary nPP levels can decrease growth performance and nutrient availability in poultry ( Adeola, 2018 ; Xu et al., 2019 ), consistent with the findings of the present study. One reason for the decrease in the growth performance of ducks fed a P-deficient diet was the higher Ca: nPP ratio in such diets.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorus is one of the most important minerals in poultry diets to obtain optimal productivity. In our previous study, Xu et al. (2019) found that a low nonphytate phosphorus ( nPP ) diet damaged the intestinal digestion and absorption function in Pekin duck, and low dietary nPP contents (0.22% nPP) affected the diversity of cecal microbiota and had a significant effect in modifying the bacterial community in the ceca of ducks ( Dai et al., 2018 ), which indicated that dietary P deficiency impaired the structure and function of cecal microbiome as well as intestinal health of ducks.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar with Xie et al (2009) who stated that diet contained 0.806 % Ca plus 0.403 % non-phytate phosphorus could attained the highest daily BWG and the best FCR for White Pekin ducks through the first 6 wks-old. Xu et al (2019) also showed that ducklings fed 0.22% P had minimal (P<0.05) growth while when dietary non-phytate phosphorus levels were increased led to increased (P <0.05) LBW at 14 and 21 days and BWG. Inversely, Papesova et al (2008); Nawaz et al (2008) and Rao et al (2008) mentioned non-significant improvement in BWG in birds fed low level of Ca and P. Generally, Macari et al (2002) affirmed that the optimum balance between Ca and P requirements, and their metabolic relation, provide preferable performance and development.…”
Section: Productivity Traitsmentioning
confidence: 87%
“…Also, when ducklings fed a diet that P deficiency, effect on their gut microbial communities efficiency, that convert more need to obtain P phytate (Dai et al, 2018), requiring that more energy is spent on the life maintenance and decrease available energy to growth (Zeng et al, 2015). These results are harmony with Xu et al (2019) who announced, ducklings fed 0.22% P had lower feed intake and nutrients utilization, while increasing dietary levels of non-phytate phosphorus led to increase (P<0.05) feed intake and improve FCR.…”
Section: Productivity Traitsmentioning
confidence: 91%
“…Available literature data show that corticosterone reduces absorption of phosphates into the enterocytes and then into the bloodstream [23], but this effect was not noted in our study. Intestinal absorption and accumulation of phosphates in tissues may also be regulated by other hormones, including PTH, insulin, and dopamine, whose secretion is influenced by Cr [23,40]. Our previous research [5] has shown that the addition of Cr to the diet of chickens in the form of both Cr-Pic and Cr-NP increases insulin secretion, while the addition of Cr in the form of Cr-NP increases plasma dopamine levels.…”
Section: Discussionmentioning
confidence: 99%